EFFECT OF STEAM TEMPERATURE ON YARN MOISTURE REGULATION IN TEXTILE INDUSTRY - Sharibaev, Nosir; Mirzabaev, Badriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This paper examines steam temperature and its effect on moisture management properties in textile yarns. How steam temperature affects moisture uptake and release processes is examined, and effective management techniques to improve fabric quality are analyzed. Research is important for the introduction of new technologies in textile production.